Contrasting Carbon Allocation Strategies of Ring-Porous and Diffuse-Porous Species Converge Toward Similar Growth Responses to Drought - Buttó, Valentina; Millan, Mathilde; Rossi, Sergio; Delagrange, Sylvain (Frontiers in Plant Science, 2021)
Extreme climatic events that are expected under global warming expose forest ecosystems to drought stress, which may affect growth and productivity. We assessed intra-annual growth responses of trees to soil water content in species belonging to different functional groups of tree-ring porosity. We pose the hypothesis that species with contrasting carbon allocation strategies, which emerge from different relationships between wood traits and canopy architecture, display divergent growth responses to drought. We selected two diffuse-porous species (Acer saccharum, Betula alleghanensis) and two ring-porous species (Quercus rubra, Fraxinus americana) from the mixed forest of Quebec (Canada). We measured anatomical wood traits and canopy architecture in eight individuals per species, and assessed tree-growth sensitivity to water balance during 2008-2017 using the Standardized Precipitation Evapotranspiration index (SPEI). Stem elongation in diffuse-porous species mainly depended upon total number of ramifications, and on hydraulic diameter of the tree-ring vessels. In ring-porous species, stem elongation mainly depended upon productivity of the current year, i.e., number of vessels and basal area increment. Diffuse-porous and ring-porous species had similar responses to soil water balance. The effect of soil water balance on tree growth changed during the growing season. In April, decreasing soil temperature linked to wet conditions could explain the negative relationship between SPEI and tree growth. In late spring, greater water availability affected carbon partitioning, by promoting the formation of larger xylem vessels in both functional groups. Results suggest that timings and duration of drought events affect meristem growth and carbon allocation in both functional groups. Drought induces the formation of fewer xylem vessels in ring-porous species, and smaller xylem vessels in diffuse-porous species, the latter being also prone to a decline in stem elongation due to a reduced number of ramifications. Indeed, stem elongation of diffuse-porous species is influenced by environmental conditions of the previous year, which determine the total number of ramifications during the current year. Drought responses in different functional groups are thus characterized by different drivers, express contrasting levels of resistance or resilience, but finally result in an overall similar loss of productivity.